Pengaruh Kompensasi dan Disiplin Kerja Terhadap Kinerja Dosen di Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri - Agustina Heryati (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2017)
This study aimed to analyze the effect of compensation and discipline, and work on the performance lecturer at the Sekolah Tinggi Ekonomi Bisnis Syariah (STEBIS). Respondents of this research is the foundation of tenured faculty at the Sekolah Tinggi Ekonomi Bisnis Syariah (STEBIS). Data collected consist of primary data and secondary data. Secondary data were obtained from several sources such as journals, books, and other literature. Primary data were obtained through questionnaires distributed to respondents. By using purposive sampling techniques, obtained 60 respondents. Testing of statistical analysis used include validity, reliability, and classical assumption. The results of multiple linear regression analysis showed that compensation and work discipline has a positive and significant impact on the faculty at the University Indo Global Mandiri either simultan or partial. The results of this study are expected to be used as input for the Sekolah Tinggi Ekonomi Bisnis Syariah (STEBIS) to be able to create compensation and discipline, and work to improve the performance of lecturers. For further study, the researchers also suggested to incorporate other variables in this study.